Cardiovascular disease (CVD) risk scores, age, or years since menopause to predict cardiovascular disease in the Women's Health Initiative. Issue 6 (June 2021) - Wild, Robert A.; Hovey, Kathleen M.; Andrews, Christopher; Robinson, Jennifer G.; Kaunitz, Andrew M.; Manson, JoAnn E.; Crandall, Carolyn J.; Paragallo, Rachel; Shufelt, Chrisandra; Merz, C. Noel Bairey
Abstract: Objective: To assess the utility of cardiovascular disease (CVD) risk scores compared to age or years since menopause for prediction of CVD events in the WHI clinical trials. Methods: Briefly, in the randomized clinical trial 27, 347 postmenopausal women age 50 to 79 years entered from 1993 to 1998. Women with a uterus (16, 608) were randomized to receive daily oral conjugated equine estrogen (CEE) (0.625 mg) plus medroxyprogesterone acetate (2.5 mg) (5.7 years or placebo), while women with a hysterectomy (10, 739) were randomized to receive daily oral CEE (0.625 mg) alone or placebo (7.2 y). CVD risk scores were assessed at baseline and CVD events were adjudicated throughout the follow-up period to the end of the main study phase and to the end of cumulative follow-up. The median follow-up time after the start of the randomized clinical trial to the end of the main study phase was 8.2 years. The median follow-up time to the end of cumulative follow-up was 17.6 years. We compared The American Heart Association/American College of Cardiology (AHA/ACC) and Framingham Heart Study risk scores to age or years since menopause all obtained at baseline to predict subsequent CVD events. The absolute event rates, hazard ratios, and C-statistics (Uno Concordance from Cox proportional models) were compared. Results: Overall, the hazard ratios for CVD events were highest with calculated CVD scores calculated at trial onset both at the end of the main study (ranging from 2.02 to 10.8 for Q2-Q5, compared to Q1) and at cumulative follow-up (ranging from 1.76 to 8.86 for Q2-Q5, compared to Q1). While older age and years since menopause at baseline were also associated with higher CVD event rates, better risk prediction was accomplished by using CVD risk scores. The Framingham Heart Study BMI score had the highest C-statistic at the end of the main study (0.711) and after 17.6 years through the end of follow-up (0.689). Conclusions: CVD risk scores can help identify postmenopausal women at higher risk for CVD beyond age or time since menopause. Risk scoring that better estimates vascular aging may facilitate CVD risk prevention. When performed prior to initiation of menopausal hormone therapy, scores can better inform HT risk/benefit discussions. N/A: Video Summary: http://links.lww.com/MENO/A717 . Abstract : Supplemental Digital Content is available in the text